PENERAPAN PPN MASUKAN DAN PPN KELUARAN PADA PT.KARYA MANDALA PUTERA SULAWESI SELATAN - Fitriani, Fitriani; Rustam, Andi; Amran, Amran (Invoice : Jurnal Ilmu Akuntansi, 2019)
This study aims to assets whether the application of value and added tax value and value added tax on PT.The work of the mandala son has been in accordance with the tax laws in 2017.The type of research used in this research is case study with quantitative descriptive approach.The data is processed Lis tax output and input on PT.Work mandala son of 2017 obtained from tax reports such as value added tax during the year 2017.while the data analysis techniques used in the study is to collect the necessary data that comes from the company and then describes it as a whole. Based on the results of data processing can be concluded that appilacation of value added tax on PT.Work of the mandala son for collection,recording,reporting is in accordance with the law number 42 of 2009 regarding value added tax.